2021
DOI: 10.1039/d1ra07041j
|View full text |Cite
|
Sign up to set email alerts
|

Dalpulapans A–E from the roots of Dalbergia stipulacea

Abstract: Five new compounds, dalpulapans A–E (1–5), were isolated from the hexane extract of the roots of Dalbergia stipulacea Roxb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…8 The chemical constituents from the stems and the roots of this plant are chalcones, isoflavonoids, flavonoids, pterocarpans, diterpenes and coumarins. 9–11 R , R -Velucarpin A, a pterocarpan, from the roots of this plant showed cytotoxicity against HeLa cells with an IC 50 value of 10.9 ± 0.42 μM (Posri et al , 2021). 9 (−)-12α-hydroxyrotenone from the methanol extract of D. stipulacea roots displayed cytotoxicity against HepG2 cell line with an IC 50 value of 18.01 ± 1.51 mM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The chemical constituents from the stems and the roots of this plant are chalcones, isoflavonoids, flavonoids, pterocarpans, diterpenes and coumarins. 9–11 R , R -Velucarpin A, a pterocarpan, from the roots of this plant showed cytotoxicity against HeLa cells with an IC 50 value of 10.9 ± 0.42 μM (Posri et al , 2021). 9 (−)-12α-hydroxyrotenone from the methanol extract of D. stipulacea roots displayed cytotoxicity against HepG2 cell line with an IC 50 value of 18.01 ± 1.51 mM.…”
Section: Introductionmentioning
confidence: 99%
“…9–11 R , R -Velucarpin A, a pterocarpan, from the roots of this plant showed cytotoxicity against HeLa cells with an IC 50 value of 10.9 ± 0.42 μM (Posri et al , 2021). 9 (−)-12α-hydroxyrotenone from the methanol extract of D. stipulacea roots displayed cytotoxicity against HepG2 cell line with an IC 50 value of 18.01 ± 1.51 mM. 10 It was found that (−)-vestitol from the stems of this plant displayed the strongest antifungal activity against Pythium insidiosum and had higher activity than the amphotericin-B standard.…”
Section: Introductionmentioning
confidence: 99%